Predicting Peer to Peer Lending Loan Risk Using Classification Approach - Zulfikri, Fahmi; Tryanda, Dendy; Syarif, Allevia; Patria, Harry (SOTVI, 2021)
Technological innovations have affected all sectors of life, especially, the financial sector with the emergence of financial technology. One of them is marked by the emergence of Peer-to-Peer Lending (